Hermeneutic Strategies in Globalized Translation (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores how literary translators dismantle or preserve imagery when they carry metaphor across languages in an era of accelerated global exchange. Drawing on hermeneutic philosophy and current descriptive studies, it shows that metaphorical meaning is rarely “carried over” intact; instead, translators practise selective metaphorical reframing – a spectrum of interventions that replace, unfold, or silence figurative images to keep narrative horizons open for new readers. Bringing together case analyses from Arabic-to-English, English-to-Uzbek and Kurdish-to-English translation, the discussion demonstrates that reframing is governed by the translator’s historical pre-understanding and by the cultural affordances of the target polysystem. Implications are offered for training, ethics and digital tools.